A conformable fractional calculus on arbitrary time scales - Benkhettou, Nadia (2016)
A conformable time-scale fractional calculus of order α. ∈]0, 1] is introduced. The basic tools for fractional differentiation and fractional integration are then developed. The Hilger time-scale calculus is obtained as a particular case, by choosing α. =. 1. © 2015 The Authors.